2020
DOI: 10.1038/s41598-020-61386-4
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of macular edema in excessive morning blood pressure surge in patients with retinal vein occlusion

Abstract: Morning blood pressure surge (MBPS) had been known to be associated with hypertensive target organ injury and vascular events. Retinal vein occlusion (RVO) is also known to be related with underlying cardiovascular risk factors. This study investigated the effect of MBPS on patients with RVO. In total, 76 patients with RVO who had undergone systemic cardiovascular examination including a 24-hour ambulatory blood pressure monitoring, carotid artery intima media thickness, and pulse wave velocity were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In our study, we found that bilateral CIMT values in patients with RVO were significantly thicker, suggesting that patients with RVO should be evaluated using carotid Doppler ultrasound. In contrast to these studies, Kim et al reported that PWV and CIMT parameters were not associated with RVO ( 24 ).…”
Section: Discussionmentioning
confidence: 90%
“…In our study, we found that bilateral CIMT values in patients with RVO were significantly thicker, suggesting that patients with RVO should be evaluated using carotid Doppler ultrasound. In contrast to these studies, Kim et al reported that PWV and CIMT parameters were not associated with RVO ( 24 ).…”
Section: Discussionmentioning
confidence: 90%
“…According to literature reports, [1][2][3][4][5][6][7][8][9][10][11] retinal vein occlusion (RVO), including branch retinal vein occlusion (BRVO) and central retinal vein occlusion (CRVO), has the strongest correlation with hypertension, 1 followed by diabetes, hyperlipidemia, hospital-treated ischemic heart disease, obstructive sleep apnea, morning blood pressure surge, glaucoma, thrombophilia and hypercoagulation, systemic and inflammatory diseases, retinal vasculitis, pseudotumor cerebri, crowded optic disc, endothelin-1 and medications. The current first-line treatment for retinal vein occlusion related macular edema (RVO-ME) is intravitreal injection (IVI) of anti-vascular endothelial growth factor (VEGF) medicine, 2,3,12,13 or dexamethasone (DEX) implant.…”
mentioning
confidence: 99%